In Vivo Demonstration of the Superior Replication and Infectivity of Genotype 2.1 with Respect to Genotype 3.4 of Classical Swine Fever Virus by Dual Infections - Huang, Yu-Liang (Pathogens, 2020)
In Taiwan, the prevalent CSFV population has shifted from the historical genotype 3.4 (94.4 strain) to the newly invading genotype 2.1 (TD/96 strain) since 1996. This study analyzed the competition between these two virus genotypes in dual infection pigs with equal and different virus populations and with maternally derived neutralizing antibodies induced by a third genotype of modified live vaccine (MLV), to simulate that occurring in natural situations in the field. Experimentally, under various dual infection conditions, with or without the presence of maternal antibodies, with various specimens from blood, oral and fecal swabs, and internal organs at various time points, the TD/96 had consistently 1.51−3.08 log higher loads than those of 94.4. A second passage of competition in the same animals further widened the lead of TD/96 as indicated by viral loads. The maternally derived antibodies provided partial protection to both wild type CSFVs and was correlated with lower clinical scores, febrile reaction, and animal mortality. In the presence of maternal antibodies, pigs could be infected by both wild type CSFVs, with TD/96 dominating. These findings partially explain the CSFV shift observed, furthering our understanding of CSFV pathogenesis in the field, and are helpful for the control of CSF.